Exploring moral values of the main character in “Dead Poets Society” - Qaniu, Fitrahmel Razaq; Sarair, Sarair; Netta, Ayuna (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2024)
This study conducted a qualitative analysis of the moral values depicted by the main character in the movie